Using of Constructed Wetlands in The Treatment of Wastewater: A Review for Operation and Performance (Journal of Engineering, 2023)
Wastewater recycling for non-potable uses has gained significant attention to mitigate the high pressure on freshwater resources. This requires using a sustainable technique to treat natural municipal wastewater as an alternative to conventional methods, especially in arid and semi-arid rural areas. One of the promising techniques applied to satisfy the objective of wastewater reuse is the constructed wetlands (CWs) which have been used extensively in most countries worldwide through the last decades. The present study introduces a significant review of the definition, classification, and components of CWs, identifying the mechanisms controlling the removal process within such units. Vertical, horizontal, and hybrid CWs were used to treat different types of wastewater from individual households, waste disposal sites, oil refineries, agricultural production, and tannery effluent. The effects of several design and operational factors related to the type of plant, substrate, and flow direction are studied and surveyed in this work to be the starting point for researchers in future investigations